Case report of multiple hepatic microabscesses in a term neonate - Bafna, Sanjay; Kirthana, S B; Bafna, Vibha; Lad, Sagar; Ravikanth, Mergu (Indian Journal of Child Health, 2018)
Neonatal liver abscess is a rare entity, which usually occurs in preterm infants with sepsis and certain risk factors like umbilical vein catheterization. Neonatal hepatic abscess has a non-specific clinical presentation, and a high index of suspicion for this condition is warranted in case of unresolving sepsis especially in the presence of risk factors. Ultrasonography of abdomen is an important investigation in a febrile neonate with sepsis. Here, we report a case of hepatic microabscesses in a term neonate without any significant risk factors. We want to report this case because of its rare occurrence particularly in a term neonate without significant risk factors. This case also emphasizes the utility of abdominal ultrasonography in a febrile neonate with unresolving sepsis.